Sprint decrement during a simulated rugby sevens tournament is more related to lactate threshold than aerobic capacity - Hennessy, Richard (2022)
Rugby sevens is a sport with diverse physiological demands as aerobic fitness, sprint velocity and contact skills each have a significant impact on performance. Training for speed is an important part of physical preparation, but athletes often are unable to attain peak velocity during match play. Understanding the relationship between aerobic capacity and recovery between individual sprints and games may influence training practices. The purpose of the study was to examine the link between indicators of aerobic fitness and sprint decrements during a simulated rugby sevens tournament to guide training practices.